'In favour of a strong Europe' – what does this mean?. Issue 1 (June 2014) - Habermas, Jürgen
<x xml:space="preserve">Abstract</x> In a speech to members of the German Social Democratic party (SPD) in February 2014, philosopher and sociologist Jürgen Habermas outlined his vision for Europe, tackling the three major contemporary crises: German domination, European legitimacy and political union.